The Expertise of Korean manpower (Seoul, Korea, 1983)
Contents: Winning skills; national development and skilled manpower; developing skilled manpower through vocational training; a bright future for Korean skills
Keywords: Labor supply,Cung ứng lao động; Skilled labor,Lao động lành nghề; Korea (South),Nam Triều Tiên